2019
DOI: 10.1177/2280800019836830
|View full text |Cite
|
Sign up to set email alerts
|

Design, manufacture, and fatigue analysis of lightweight hip implants

Abstract: Background: This study aims to design, analyze and manufacture lightweight hip implants which have sufficient fatigue performance to enable use in total hip arthroplasty (THA). Methods: The lattice structure was applied on an implant geometry, which is frequently used in THA, to provide a reduction in mass and increase flexibility. The implant surfaces were roughened using semispherical pores to improve the osseointegration. The specimens were manufactured by means of direct metal laser sintering (DMLS) and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…Maximum VM stresses and high displacement occur in the upper region of all cellular implants. These results show that it is similar to the ones introduced by Sivasankar et al and Delikanli et al [59,60]. As shown in Table 5 and Figure 9, the less porosity cellular implant (optimized) contains the smallest maximumVM stresses (533.81 MPa) compared to the higher porosity cellular implant.…”
Section: Simulation Resultssupporting
confidence: 87%
“…Maximum VM stresses and high displacement occur in the upper region of all cellular implants. These results show that it is similar to the ones introduced by Sivasankar et al and Delikanli et al [59,60]. As shown in Table 5 and Figure 9, the less porosity cellular implant (optimized) contains the smallest maximumVM stresses (533.81 MPa) compared to the higher porosity cellular implant.…”
Section: Simulation Resultssupporting
confidence: 87%
“…In 2019, Chethan et al 15 used FEM to study the static physical structure of several models of femoral nails and acetabular components for THA and concluded that the trapezoidal femoral components suffer less strain; ceramic acetabular inserts, on the other hand, showed better mechanical properties under load. Finite element method was validated as an alternative method to traditional physical tests on hip prostheses by Delikanli and Kayacan 16 in 2019; their study compared the behavior of a titanium femoral stem under load in a physical model and FEM, with similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Another AM design was proposed by Delikanli et al in 2019. A solid lattice structure with variable sizing in the inner part and semi-spherical pores in the outer region was modelled and manufactured [14]. A reduction of 15-17% of the implant mass was obtained and the proposed manufacture reports enough fatigue performance according to the requirements of the ISO 7206 standard.…”
Section: Introductionmentioning
confidence: 99%